Effects of Family Socioeconomic Status on Parents' Views Concerning the Integration of Computers into Preschool Classrooms. - Natsiopoulou, Triantafillia; Melissa-Halikiopoulou, Chrisoula; Lioliou, Chrysanthi (International Journal of Caring Sciences)
Background: The rapid growth of ICT has led to an important increase in the use of computers in preschool age. However the benefits of this use are a debatable issue. Some focus on the positive effects of computers on learning and kids' cognitive development while others believe that computers may negatively affect their social and motivational impact. Aim: The aim of this research was to study Greek parents' views on preschools' computer programs and how these views are influenced by the family's socioeconomic level. Methodology: The survey involved 280 parents of children aged 3-5 years, of whom 140 were in the upper socioeconomic level and the other 140 in a lower one. Results: The upper socioeconomic level parents thought that the use of computers was appropriate for preschool children more than parents of lower socioeconomic status (P=0.01). and that its inclusion in the preschool center's program would work in favor for children who have no computer at home (P=0.00). Parents with higher socioeconomic status felt more than the others that such a program can support the provision of knowledge (P=0.00), the development of mathematical (P=0.00) and linguistic skills (P=0.00) and entertain children (P=0.04). Furthermore, the upper socioeconomic level parents as opposed to the other group do not consider that the computer will remove preschool educator from their leading and teaching role (P=0.04) or reduce their communication with the preschoolers (P=0.00). Conclusions: The results of this study revealed that Greek parents, especially those of higher socioeconomic level, have a positive view on the integration of a computer program into the preschool classroom.